Association of systemic immune-inflammatory index with all-cause and cancer mortality in Americans aged 60 years and older - Lu, Wangfeng; Gong, Yuliang; Liu, Lei; Zhang, Yonghong; Tian, Xiaojian; Liu, Huanxian (Frontiers in Aging, 2025)
BackgroundThis research delved into the association between the systemic immune-inflammatory index (SII) and both all-cause and cancer-specific mortality among individuals aged 60 years and above in the United States during the period from 1999 to 2018, with follow-up extending until 31 December 2019. The data utilized was sourced from 4295 population-based participants in the National Health and Nutrition Examination Survey (NHANES).MethodsTo analyze the relationship between SII and mortality, the study employed Cox proportional-risk models, restricted cubic spline curves, survival curves, and subgroup analyses.ResultsThe average age of the participants was 70.7 (±7.6) years, the median follow-up duration was 131.7 (±59.8) months, and the all-cause mortality rate stood at 50.5%. Findings from the Cox regression model indicated that, after adjusting for covariates, SII was significantly and linearly related to all-cause mortality (hazard ratio HR = 1.31, 95% confidence interval CI = 1.15–1.48). Moreover, the relationship between SII and cancer mortality exhibited a U-shaped pattern. Results from the survival curves suggested that a higher SII was associated with an augmented risk of both all-cause mortality and cancer mortality.ConclusionThere is a significant association between higher SII levels and increased risk of all-cause and cancer-specific mortality in the US population aged 60 years and older.